ROLE OF THE SUPERFICIAL CONSISTING OF PROCESSES OF FORMATION OF MAXIMUM LAYERS OF ANTIFRICTSIYNIH LIQUIDS - Мельник, Петро Іванович; Крамар, Валерій Максимович; Цідило, Іван Васильович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
On the basis of performances about existence of surface states in chips is given interpretation of the gear of formation of a limiting seam in lubricating liquids, which one will be used for elimination of dry friction between surfaces of parts of gears.